Overcome social anxiety disorder and develop visionary leadership in uncertain environments: The important role of psychological resilience - Guan, Yi; Wang, Yao; Zhang, Jiaojiao; Cao, Yuan (Frontiers in Psychology, 2023)
Uncertainty is the main feature of the business environment in the post-coronavirus disease 2019 (COVID-19) era. People taking leadership positions in an uncertain environment constantly encounter unprecedented risks and challenges. Many of them have difficulties adapting to such an environment and thus experience severe anxiety, showing the symptoms of social anxiety disorder (SAD), failing to exert effective leadership in social interaction contexts. How can leaders overcome SAD and effectively motivate their subordinates in an uncertain environment? This study explores the important role of psychological resilience. Using sample data collected from 82 leaders and 363 subordinates of eight enterprises in China from May to June 2020, the current study reveals that a high degree of psychological resilience enables leaders to maintain intrinsic motivated at work in an uncertain environment. Leaders with a high degree of psychological resilience perform better in identifying the organizations’ vision and displaying visionary leadership than those with a low degree. The current study enriches the knowledge of leaders’ psychological well-being and effective leadership in the post-COVID-19 era.